Evaluation of anti-Mullerian hormone in regular and repeat breeding Murrah buffaloes during estrous cycle - KEKAN, P M; INGOLE, S D; NAGVEKAR, A S; BHARUCHA, S V; KHARDE, S D (The Indian Journal of Animal Sciences, 2020)
The objective of the study was to evaluate AMH concentration in repeat breeding Murrah buffaloes. Two groups of regular and repeat breeding were formed, each group consist of six buffalo animals. Blood samples were collected on 7th, 14th and 21st day of estrous cycle and after centrifugation serum was stored in refrigerator at â€“20Â°C until analysis of AMH. The result showed non-significantly higher mean values of AMH in cyclic buffaloes than repeat breeders on 7th 14th and 21st day of estrous cycle. Therefore, it is concluded that AMH may not be the cause of infertility in repeat breeders. Repeat breeding buffaloes may conceive but after correcting the various factors of infertility.